Hubungan Asupan Mikronutrien dan Status Gizi Anak Usia 2-5 Tahun di Wilayah Posyandu Gonilan - Rismiati, Rismiati; , dr. M. Shoim Dasuki, M.Kes; , dr. Anika Candrasari, M.Kes (2016)
The best period of children growth and development are before 5th year (golden period). One of the factor that affected growth is food intake. Food intake divided into macronutrients and micronutrients. Deficiency of specific micronutrient such as vitamin A, iron and zinc increase the risk of child death. In 2012, 52 million of children under 5 year in this world are malnutrition. In 2013, the prevalency of national underweight of children under 5 year are 19,6%.To analyzed micronutrients intake of children age 2-5 in posyandu Gonilan's area.Using analitycal observational study design with cross sectional approach. Samples in this study are children age 2-5 in posyandu Gonilan's area and the number of the samples are 39 childs. Samples were chosen with purposive sampling technique. Vitamin A, iron and zinc intake assessment with food recall 24 hour review technique. The assessment of nutritional status by measuring high and weight of child and then analyzed with standard of WHO 2005. Correlation between variables were analyzed using Chi Square test.Based on fisher test vitamin A intake and nutritional status be obtained p=0,045, between iron intake and nutritional status be obtained p=0,022, between zinc intake and nutritional status be obtained p=0,023. There is a correlation between vitamin A, iron intake, zinc intake and nutritional status of children age 2-5 in posyandu Gonilan's area.